REVITALISASI KAWASAN CITRA NIAGA SAMARINDA - Gazali, Irsan (ARTEKS Jurnal Teknik Arsitektur, 2017)
Title: Revitalization of Citra Niaga Samarinda Arena promotions and shopping centers nowadays called Citra Niaga as an icon of the capital of Samarinda, which was built in 1984. The design of Citra Niaga is directed to the concept of "Night Market" which makes Citra Niaga as a business space and recreation areas for the attractive public. But in a fact, the icon of Samarinda is not desirable again by the public because they have an issue that makes this icon become weak and has not good quality or as a good public space standardization (Issue of Concern), such as security, safety, health, attraction, comfort, accessibility and also raciness . And to comply those criteria, it should be have good components (Scope of Issue), for this research it can be used qualitative descriptive method it based on the fact in the field and also the real evidence. This approach based on revitalization theory and good space public theory. For the conclusion, the standardization, a space of quality must have normative criteria so a space public can be survive. So that, this functioned as revitalization concept in effort to revitalization Citra Niaga. Keywords: citra niaga, icon, city, publik space, revitalization